Bibliographic and content analysis of physics papers from North Korea indexed in the Scopus from 2005 to 2018 - Kim, Kihong; Chung, Yeonok (Science Editing, 2019)
Purpose: It aimed at assessing the current status of physics research in North Korea through a bibliographic and content analysis of the physics papers from North Korea indexed in the Scopus from 2005 to 2018. Methods: The Scopus was searched on January 18, 2019 by using the search option 'Affiliation city' with "Pyongyang OR Chongjin OR Hamhung OR Sariwon OR Wonsan OR Kimchaek" as the city name and 171 physics papers from North Korea written in English were identified. By performing supplementary searches based on the author names and the references, 46 papers belonging to physics were added and the total of 217 papers were identified. They were classified by publication year, co-authors' country, institution, subfield, journal and author. Representative North Korean physicists and the active subfields of physics were identified. Results: The number of physics papers from North Korea has been growing rapidly in the recent years. Physics research activities in North Korea were extremely centralized in its capital, Pyongyang, where all major research institutions were located. Major research areas included condensed matter physics, optics and high energy physics and the large majority of papers were theoretical ones. From a bibliographic and content analysis, sixteen representative or notable physicists in North Korea were identified. Conclusion: It appears that the North Korean government is actively encouraging researchers to publish more papers in international journals. There is a strong growth potential in physics research in North Korea. In order to achieve balanced development in physics, it is an important task to build competitive experimental groups.
Keywords: Bibliography; North Korea; Physics research